Responding to fiscal stress: a state-wide survey of local governments in Louisiana: a research note - Ward, James D. (2001)
The early 1980s represented an era where fiscal stress, cutback management and retrenchment strategies captured the attention of public administration scholars and practitioners. Yet, lessons learned from that era should not be forgotten. This research note, containing information from a 1990s survey of Louisiana local governments, supports the position that rural governments suffer hardest in bad economic times and that precautionary measures should thus be taken to lessen the budgetary shortfalls which often result in either the cutback or the total elimination of services. - Reproduced
Keywords: Local government